2020
DOI: 10.12659/msm.921303
|View full text |Cite
|
Sign up to set email alerts
|

Does Exposure to Computed Tomography Contrast Media Increase Risk of End-Stage Renal Disease?

Abstract: Departmental sources Background:There are many studies on acute kidney injury (AKI) after exposure to contrast media in patients with chronic kidney disease (CKD). However, whether the risk of end-stage renal disease (ESRD) increases after exposure to contrast media in the long term, regardless of development of AKI after such exposure, has not been studied. Material/Methods:The electronic health records of patients diagnosed with CKD and followed up from 2014 to 2018 at a tertiary university hospital were ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…These imaging techniques use harsh iodine contrast, compared to the preferred gadolinium medium (which is metal-based), as CT contrast can damage the kidneys. One study found gadolinium is associated with a lower incidence of contrast nephropathy and early progression to end-stage renal disease in patients with pre-existing chronic kidney disease ( 75 ). However, other studies found that the real-life risk is insignificant by undergoing precautions ( 76 ).…”
Section: Cardiac Ctmentioning
confidence: 99%
“…These imaging techniques use harsh iodine contrast, compared to the preferred gadolinium medium (which is metal-based), as CT contrast can damage the kidneys. One study found gadolinium is associated with a lower incidence of contrast nephropathy and early progression to end-stage renal disease in patients with pre-existing chronic kidney disease ( 75 ). However, other studies found that the real-life risk is insignificant by undergoing precautions ( 76 ).…”
Section: Cardiac Ctmentioning
confidence: 99%
“…Although it ability to measure SK-GFR as well as the potential of CT angiography in renal function assessment in CKD patients, CT is still limited to ionizing radiation and contrast agent injection that can injure the kidney (Lerman et al, 1996;Maioli et al, 2012). Recently, Contrast-Enhanced CT was reported to increase the risk of End-Stage Renal Disease (ESRD) (Lim et al, 2020). However, identification of renal fibrosis or perfusion with non-contrast CT remains challenging (Zhu et al, 2018).…”
Section: Computed Tomographymentioning
confidence: 99%
“…Like NSAIDs, AKI secondary to contrast use is now considered relatively rare in patients with higher eGFRs [26,28]. In those with existing CKD, contrast exposure has been associated with nephropathy and progression to ESKD in small studies [29,30]. Less is known about the association of contrast exposures with incident CKD.…”
Section: Introductionmentioning
confidence: 99%